The application of Plant Growth Promoting Rhizobacteria and Organic Matters from Black Soldier Fly Larva Culture, Calliandra, Cocopeat in the Pre-nursery Oil Palm Seedling - Theresia Maria Astuti Yohana; Christian Simanjuntak Michael; Pratama Putra Dian; Iqrar Irum; Ekawati Ida (E3S Web of Conferences, 2023)
Plant growth promoting rhizobacteria (PGPR) are some of the bacteria that live in the rhizosphere. This research was aimed to evaluated the effect of the application of PGPR and various organic matter from black soldier fly larvae (BSF) tehnology, calliandra humus and cocopeat on the growth of pre-nursery oil palm. The research was conducted in Maguwoharjo, Depok, Sleman, Yogyakarta in April to July 2020. The research used factorial experimental method arranged in a completely randomized design (CRD) which consisted of two factors. The first factor is the concentration of PGPR which consists of four levels namely control (without PGPR), PGPR 10 mL polybag-1, 20 mL polybag-1, and 30 mL polybag-1. The second factor is various of organic matter consisting of four levels namely: control (without organic matter), organic matter from BSF larvae technology, calliandra humus and cocopeat. The research data were analyzed using analysis of varians (ANOVA) and follow up test with DMRT. The results showed that the various of organic matter affect the pre-nursery oil palm growth, the best is Calliandra humus. The PGPR application was able to increase the growth of pre nursery oil palm seedlings, the best dose is 10 mL polybag-1.